2022
DOI: 10.3390/mi13010125
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Responsive Conductive Poly(vinyl alcohol) Composites Containing Waste Cotton Fibers Biochar

Abstract: The development of responsive composite materials is among the most interesting challenges in contemporary material science and technology. Nevertheless, the use of highly expensive nanostructured fillers has slowed down the spread of these smart materials in several key productive sectors. Here, we propose a new piezoresistive PVA composite containing a cheap, conductive, waste-derived, cotton biochar. We evaluated the electromagnetic properties of the composites under both AC and DC regimes and as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…This decrease indicated that the applied pressure induced the film deformation, and this feature was responsible for the formation of a higher number of conductive paths, which increase the conductivity. Similar results were achieved by Bartoli et al [110], who dispersed biochar derived from waste cotton into PVA, achieving a conductivity of up to 16 S/m under a pressure of 750 bar.…”
Section: Other Thermoplastic-based Compositessupporting
confidence: 86%
“…This decrease indicated that the applied pressure induced the film deformation, and this feature was responsible for the formation of a higher number of conductive paths, which increase the conductivity. Similar results were achieved by Bartoli et al [110], who dispersed biochar derived from waste cotton into PVA, achieving a conductivity of up to 16 S/m under a pressure of 750 bar.…”
Section: Other Thermoplastic-based Compositessupporting
confidence: 86%
“…The observed conductivity values are comparable with those reported for loading exceeding 15 wt% of coffee-derived biochar dispersed into an epoxy matrix [24], but considerably lower compared to cotton-derived biochar fibers produced at 1000 °C and dispersed into poly(vinyl alcohol) [23]. The improvement upon coffee-derived biochar is reasonably due to the aspect ratio of the HFB that allowed to reach percolation threshold in a more effective way.…”
Section: Characterization Of Epoxy/hemp Fiber Biochar Compositessupporting
confidence: 79%
“…As shown in Fig. 3b, W is constant at low T and it mildly increases at higher T, whereas W would decrease with increasing T in hopping-type transport-as so far observed in biochars derived from the pyrolysis of cotton fibers only [23]. In agreement with Pukha et al [45], we therefore exclude charge-carrier hopping as a significant source of conductivity in HFB and ascribe its dominant DC electric transport mechanism to direct tunneling between graphite nanocrystals across sp 3 boundaries.…”
Section: Characterization Of Hfbsupporting
confidence: 61%
See 1 more Smart Citation
“…Journal of Nanomaterials their increased functionality, controllability, and biocompatibility [12][13][14][15][16].…”
Section: Two-dimensional Smart Membrane Advancementmentioning
confidence: 99%